Unconsidered but influencing interference in unmanned aerial vehicle cabling system - Setyadewi, Imas Tri; Prabowo, Yanuar; Wibowo, Priyo; Priambodo, Purnomo Sidi (International Journal of Electrical and Computer Engineering (IJECE), 2024)
The increasing complexity of electrical and electronic systems in unmanned aerial vehicles (UAVs) has raised concerns regarding unwanted electromagnetic interference (EMI) due to limited compartment space. Recent studies have highlighted the UAV cabling as the primary pathway for interference. This paper presents a novel approach to investigating the effects of interference power, polarization angle, and distance from the interference source on EMI in UAV cable systems. Measurements and simulations were performed to analyze the influence of these factors on the radiation received by the cable. A linear dipole antenna, operating at a frequency of 905 MHz, served as the radiation source, while a single wire cable pair terminated with a 50-ohm resistor was employed as the victim. The findings reveal that the power transmitted by the source, the distance between the cable and the source, and the polarization angle have a significant impact on the electromagnetic interference received by the cable. Notably, a perpendicular orientation of the cable to the interference source (antenna) in the far-field yielded a reduction of up to 15 dBm in EMI. The results underscore the necessity for more sophisticated models and comprehensive measurements to fully comprehend the diverse factors affecting polarization losses in practical scenarios.